Effects on the transient energy distribution of turbocharging mode switching for marine diesel engines. (15th June 2022) - Leng, Ling; Qiu, Hongjian; Li, Xiannan; Zhong, Jie; Shi, Lei; Deng, Kangyao
Abstract: Nowadays, the high-power density and high efficiency of marine diesel engines make the requirements of high boost pressure and wide-range intake flow increased. In this study, a two-stage sequential turbocharging (TSST) system is presented as a method for increasing the power density and broadening the efficient working range of diesel engines. Through experimental and analysis methods, the relationships of intake and exhaust energy migration and exhaust energy distribution in the turbocharging mode switching process of the TSST system are investigated, and the optimal control strategy for the switching valves is obtained. The experimental results show that the optimized valve control strategy can achieve a reasonable distribution and efficient utilization of exhaust energy during the switching process. More specifically, the boost pressure error function is only 0.0003 kPa 2 ·s, the engine speed fluctuation amplitude is less than 6 r/min, and the speed transition time is less than 8 s. A smooth switching between the turbocharging modes of the TSST system is achieved, exhaust energy loss is minimized, and the fuel economy and power performance of marine diesel engines over the entire range of operating conditions are effectively improved. Highlights: The brake efficiency of the engine with TSST system was improved under entire conditions. Transient exhaust energy flow during the switching process was studied by experiment. The speed fluctuation first decreases and then increases with increasing delay time. Energy distribution during the switching process was optimized by valve control.